Rebirth of JUMMEC - Rosmawati, M. (2005)
The year 2005 has been magnificent.We celebrated the centennial anniversary of our university – a remarkable milestone in our history.And, after a hiatus of two years, JUMMEC is now making its long awaited comeback. We aim to make a definite presence in the University of Malaya Medical Centre.Through the publication of JUMMEC,we will be able to disseminate information and learn of each other’s work and highlight studies that are particularly relevant in our local context.